FUNGSI PENGAWASAN OLEH TENAGA PENGAWAS SEKOLAH MENENGAH PERTAMA DINAS PENDIDIKAN KABUPATEN CIAMIS DIMASA PANDEMIK COVID-19 - SABILLA, SARAH; DENGO, SALMIN; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2021)
The purpose of this study was to find out how the supervisory function of junior high school supervisors atthe Ciamis District Education Office during the covid-19 pandemic. The research was conducted usingdescriptive qualitative research methods. Sources of data used in this study are primary and secondary datawith data collection techniques namely observation, interviews, and documentation, the data obtained arethen analyzed into a conclusion from the research process. The findings of this study indicate that thefunction of implementing supervision by junior high school supervisors at the Ciamis Regency educationoffice during the covid-19 pandemic is still not good enough and implemented optimally from the fouraspects, two aspects namely the quality of the supervision program, program implementation, creativity,innovation, in the preparation of the supervisory activity/discipline program during the process ofimplementing supervision, as well as reports on program implementation and the supervisor's commitment incarrying out their duties, sensitivity to problems and their dexterity in overcoming problems are considerednot maximal enough in practice in the field, therefore it is expected that school supervisors are more improvethe quality of human resources and supervision programs as well as their commitment to the implementationof supervision so that the implementation of supervision of schools is carried out optimally in order toachieve good school quality.Keywords: Supervision Function, Supervisory Staff, Covid-19